Effect of Helicobacter Pylori Infection on Interleukin-4 and Interleukin-8 Levels in Smoker Males (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background: Smoking is a risk factor for various chronic diseases (including various infections, cancer, heart disease and respiratory diseases), and is characterized by neutrophil inflammation and the release of pro-inflammatory mediators (such as IL-8 and IL-4).  Smoking has been found to be associated with higher incidence of Helicobacter pylori and gastroduodenal diseases caused by this bacterium are a consequence of an inappropriate host's immune response.Materials& Methods: This study aimed to study the effect of smoking on certain immunological parameters, and it is a risk factor for H. pylori infection in Erbil city. The study was carried out on 71 smoker males and 20 nonsmokers. H. pylori infection and the concentration of IL-4 and IL-8 were done by ELISA Technique. P values